Automation design and analysis of the wing based on aerodynamic and structure aspect respectively - I. G.N. SUDIRA; BAMBANG K. HADI; M. A MOELYADI; DJAROT WIDAGDO (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2014)
Configuration/Geometry definition, grid generation/mashing, and modeling in wing design and analysis process usually spend much time to support calculation by computer program. Much effort has been performed by engineering group to simplify design process and also for accelerating execution time. This paper describe a method to design and analysis aerodynamic and structure of the wing by automatic technique in geometry preparation. For aerodynamic aspect, wing geometry for a certain configuration is created automatically using computer program for replacement of manual method. NWDU is the software for creating an input of “panel method base code” in the form of panel system that consist of basic input, grid point (wing coordinate) and wake point. Some aerodynamic characteristics are demonstrated in corelation with a certain wing configuration. For structural aspect, automatic technique was applied on structure modeling, including structural layout as the input of FEM analysis. Geodesic structure of wing box component was choosen as test case of the method application. Grid Generation (GG) software was developed to generate structure modeling automatically as an input of Finite Element Method (FEM)